O TRABALHO DOS POLICIAIS MILITARES DO ESPÍRITO SANTO SOB O PONTO DE VISTA DA ATIVIDADE: ANÁLISES ERGOLÓGICAS - Serrano, Edneia Vieira (2019)
This study aimed to perform the collective analysis of the military police work activity in Espírito Santo, aiming to understand how the knowledge produced in the police daily life guide the life management of these workers. To this end, the methodologica